(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The goal of this study is to find out how hotel amenities and room prices affect how satisfied guests feel about their stays. Through in-depth interviews, focus groups, observations, and case studies, the study looks at how different facilities affect tourists’ overall experience and how they think about value for money. The study also looks into how guests judge the importance of different amenities to their total image. The data show that one of the most important things that decides how happy a guest is is how well the price of the housing meets the quality of the services and facilities it offers. If people think the price is fair for what they get, they are more likely to have a good time. Including high-end amenities like spa services and delicious food makes the whole experience better for guests while keeping the important amenities. Pricing strategies and high-quality services must be used together to make customers as happy as possible. The poll also shows that guests have different tastes, which makes it even more important to be honest about how much the service costs. Here are some suggestions for hotel management: come up with a thorough plan for prices and facilities; use qualitative research to make services more relevant; and keep up with new changes in areas like technology and sustainability. This study is important for the hotel industry because it could help shape future strategies to make customers happier and keep them loyal to the brand.